Cyp3a11 metabolism-based chronotoxicity of brucine in mice. (1st October 2019) - Zhou, Ziyue; Lin, Yanke; Gao, Lu; Yang, Zemin; Wang, Shuai; Wu, Baojian
Highlights: We observed dosing time-dependent toxicity of brucine in wild-type mice. Brucine chronotoxicity was correlated with diurnal expression of Cyp3a11. Npas2 regulated Cyp3a11 metabolism and brucine chronotoxicity. Abstract: Brucine is one of the main bioactive and toxic constituents of the herb drug Semen Strychni . Here we aimed to determine dosing time-dependent hepatotoxicity of brucine, and to investigate the role of metabolism in generation of brucine chronotoxicity. Brucine was administered to wild-type or Npas2 −/− (a clock disrupted model) mice at different circadian time points for toxicity and pharmacokinetic characterization. The hepatotoxicity was evaluated by plasma alanine aminotransferase and aspartate aminotransferase measurements and histopathological analysis. The role of Cyp3a11 in brucine metabolism was determined by chemical inhibition assays and Cyp3a11-overexpressing HEK293 cells. Hepatic circadian Cyp3a11 mRNA and protein levels were determined by qPCR and Western blotting, respectively. The toxicity of brucine was more severe in the light phase [Zeitgeber time (ZT) 2 and ZT8] than in the dark phase (ZT14 and ZT20). Chemical inhibition and substrate metabolism assays suggested Cyp3a11 as a significant contributor to brucine metabolism. The Cyp3a11 mRNA, protein and activity in the livers of wild-type mice displayed significant circadian fluctuations. Npas2 ablation markedly down-regulated Cyp3a11 mRNA, protein and activity, and abrogated their circadian rhythms. The circadian time differences in brucine pharmacokinetics and liver distribution were lost in Npas2 −/− mice, so were the time differences in brucine hepatotoxicity. In conclusion, chronotoxicity of brucine was determined by circadian variations in Cyp3a11 metabolism. The findings have implications in improving brucine (and possibly Semen Strychni ) efficacy via dosing time optimization.